PENURUNAN MEDAN ELEKTROMAGNETIK MENGGUNAKAN SANGKAR FARADAY SEBAGAI MITIGASI RISIKO PELAKSANAAN ENERGISASI TRANSMISI YANG MENGALAMI SINGGUNGAN RIGHT OF WAYS (ROW) DENGAN SUMUR MIGAS - Nugroho, Aditya Widhi; Tamaji (Seminar Nasional Ilmu Terapan, 2024)
Primary energy sources such as electrical, oil and gas are energy that is really needed by society and industries. The provision process of these energy sources must adhere to applicable regulations, including the Right of Way (ROW) rules. In the case of the 500 kV Transmission Network Construction from New Aur Duri to Peranap on Sumatra Island, Indonesia, there is a regulatory conflict regarding ROW between the electricity provider (PT. PLN (Persero)) and the oil & gas provider (PT. Pertamina (Persero)), where there is a ROW tangency between transmission tower span overlaps and the free radius of the oil wells. Considering the critical need for both energy sources, the energization of the 500 kV New Aur Duri – Peranap Transmission Line must be carried out with strict of attention to safety in the vicinity of PT. Pertamina’s wells. Therefore, the Faraday Cage method will be used as one of mitigation risks of potential fires due to induced electric and magnetic fields. In this paper, the author explains the risk analysis of the energization implementation for the 500 kV New Aur Duri – Peranap Transmission and Faraday Cage construction design aimed at reducing electric field induction around PT Pertamina’s wells. By implementing this safety measure, the energization of the 500 kV New Aur Duri – Peranap Transmission Line can proceed safely, even in the overlapping ROW area.